Defects, dopants and Mg diffusion in MgTiO(3) - Kuganathan, Navaratnarajah (Sci Rep, 2019)
Magnesium titanate is technologically important due to its excellent dielectric properties required in wireless communication system. Using atomistic simulation based on the classical pair potentials we study the defect chemistry, Mg and O diffusion and a variety of dopant incorporation at Mg and Ti sites. The defect calculations suggest that cation anti-site defect is the most favourable defect process. The Mg Frenkel is the second most favourable intrinsic defect though the formation energy is highly endoergic. Higher overall activation energies (>3 eV) are observed for oxygen migration compared to those observed for magnesium (0.88 eV). Dopant substitution energies for a range of cations with charges varying from +2 to +4 were examined. Divalent dopants (Mn(2+), Fe(2+), Co(2+), Ca(2+) and Zn(2+)) on the Mg site exhibit low solution energies. Trivalent dopants prefer to occupy Mg site though their solution energies are high. Exothermic solution energies calculated for tetravalent dopants (Ge(4+) and Si(4+)) on the Ti site suggest the necessity of experimental verification.